Report on industrial attachment with Motorola Electronics Pte Ltd - Tan, Kia Poh. (2009)
This project is to help in developing a powerful online database tracking tool to track mobile phone software integration deliverables with the aim of improving efficiency, automating work flow, standardizing progress, capturing operational data, and providing real time status. This report will go through this project by first talking about all the required programming languages and software for this well organised web application, Buildweb. Then it will discuss how these languages and software work together and how web programming using these languages can make such a powerful tracking system to improve the performance and facilitate the works. Besides programming, other states of software development such as planning pseudo code, flow chart, and etc. are also included. This report is written in an understandable way that even the readers with no web programming knowledge can still understand it. It contains the author’s sharing of his personal opinions and comments which may be useful for the readers.